Health-related quality of life in children and adolescents with stroke, self-reports, and parent/proxies reports: Cross-sectional investigation - Neuner, Bruno; von Mackensen, Sylvia; Krümpel, Anne; Manner, Daniela; Friefeld, Sharon; Nixdorf, Sarah; Frühwald, Michael; deVeber, Gabrielle; Nowak-Göttl, Ulrike (Annals of neurology, 2011)
Objective: Limited data are available on health‐related quality of life (HR‐QoL) in pediatric stroke survivors. The aim of the present study was to assess HR‐QoL by self‐assessment and parent/proxy‐assessment in children and adolescents who survived a first stroke episode. Methods: We investigated HR‐QoL in pediatric stroke survivors (71 preschool children [G1] and 62 school children/adolescents [G2]) and in 169 healthy controls. HR‐QoL was assessed in patients and parents/proxies with the generic KINDL‐R questionnaire exploring overall well‐being and 6 well‐being subdimensions (physical, psychological, self‐esteem, family‐related, friend‐related, and school‐related). In pediatric stroke survivors the neurological long‐term outcome was measured with the standardized Pediatric Stroke Outcome Measure. Results: Of stroke survivors, 65% exhibited at least 1 neurologic disability. Pediatric stroke survivors reported lower overall well‐being compared with healthy controls. In G2 stroke patients, friend‐related well‐being respectively emotional well‐being was significantly reduced compared with healthy controls (73.0 vs 85.0 points; p < 0.001 respectively 80.2 vs 84.5 points; p = 0.049). Parents/proxies of both stroke survivors rated the overall well‐being and all subdimensions (except family‐related and school‐related well‐being in G1 and G2 stroke survivors and physical functioning in G2 stroke survivors) lower compared with parents/proxies of healthy children/adolescents. Overall well‐being was significantly reduced in children with moderate/severe neurological deficits compared with normal/mildly affected patients (75.5 vs 83.3 points, p = 0.01). Neonatal stroke survivors reported a significantly better neurological long‐term outcome compared to childhood stroke survivors (82.0 vs 75.0 points; p = 0.005). Interpretation: Pediatric stroke survivors compared with healthy controls are strongly affected regarding their overall well‐being and older children/adolescents regarding their well‐being with peers. Ann Neurol 2011;